Efektivitas Penerapan Multimedia Interaktif Berbasis Bookcreator Dalam Meningkatkan Hasil Belajar Bahasa Arab - Eku, Amran; Nurmawaddah, Andi; Usman, Elya Rachmi Meidina (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to test the effectiveness of the use of Bookcreator in learning Arabic compared to conventional methods in grade VIII students of MTs Harisul Khairaat Ome Islamic Boarding School, Tidore. The research uses a true-experimental design with a posttest-only control design and systematic sampling techniques. Data analysis was carried out using descriptive and inferential statistical tests. The results showed that there was no significant difference between the use of Bookcreator and the conventional method (p > 0.05). The average score of the experimental class was 79.54, while the control class was higher, which was 83.63. This study emphasizes that the effectiveness of technology-based learning media depends on the implementation, user readiness, and suitability of the method with learning objectives